Insecticidal Activities Against Odontotermes formosanus and Plutella xylostella and Corresponding Constituents of Tung Meal from Vernicia fordii - Hui Zhang; Guilin Chen; Shiyou Lü; Lin Zhang; Mingquan Guo (Insects, 2021)
The environmental pollution, pesticide resistance, and other associated problems caused by traditional chemical pesticides with limited modes of action make it urgent to seek alternative environmentally-friendly pesticides from natural products. Tung meal, the byproduct of the detoxified Vernicia fordii (Hemsl.) seed, has been commonly used as an agricultural fertilizer and as a pesticide. However, its active insecticidal extracts and ingredients remain elusive. In the present study, the contact toxicities of tung meal extracts against the agricultural and forest pests like O. formosanus and P. xylostella were examined. Our results showed that ethyl acetate and petroleum ether extracts showed the strongest toxicity against O. formosanus and P. xylostella, respectively. In order to further explore the chemical profiles of the ethyl acetate and petroleum ether extracts, UPLC-Q/TOF-MS and GC-MS analyses have been performed, and 20 and 29 compounds were identified from EA and PE extracts, respectively. The present study, for the first time, verified the noteworthy insecticidal activities on the aforementioned agricultural and forest pesticides and revealed the potential active parts and chemical composition, which are conducive to further exploiting the potential of tung meal as a natural plant-derived insecticide for biological control of agricultural and forest pests.